(untitled) (Indonesian Journal of Civil Engineering Study, 2025)
Over time construction development in Indonesia has experienced very rapid development. The purpose of construction planning is to meet project specifications which include, quality and time coupled with the realization of work safety. The purpose of this study is to find out what factors occur during the implementation and the actions taken from solving the most effective problems during the implementation of the construction of a 4-storey residential house in Graha Padma. The data collection method in this study uses questionnaires distributed to resource persons and surveys in the field to find the beginning of implementation problems. Based on the results of the research conducted, the results of the research were obtained, namely the evaluation process that was not carried out during the planning of the project implementation, including the factors that affect the implementation. Meanwhile, making a new project schedule by considering the risk factors and obstacles faced is an action taken in overcoming implementation problems.